A Study of Autonomous Weapon Systems as a Choice of Means and Methods of Warfare in Relation to the Principles Governing the Law of Armed Conflict. Case Study; Russo – Ukrainian War - Immaculate M. Achuka Abiro (Uganda Christian University, 2025)
This research will seek to give some insight on what should be done to level the ground when it comes to armed conflicts among states, keeping in mind the application of the principles of customary international humanitarian law. The development of artificial intelligence in each and every aspect and field globally means that the area of armed conflict is not an exception. In a bid to ensure complete achievement of the reasons for resorting to armed conflict, states have been seen to openly resort to the use of these autonomous weapon systems. The employment of these autonomous weapon systems in conducting war has been to a larger extent a disregard of the principles governing armed conflict. This is majorly because the law of armed conflict seeks to strike a balance between humanity and the ability to achieve the desired end for either party to the armed conflict. It should be duly noted that in order to uphold the concept of humanity, international humanitarian law runs and is based on a number of guiding principles that include the principles of humanity, distinction, discrimination, military necessity, proportionality, neutrality, as well as prohibition from causing excessive harm and superfluous injury. It should be noted that the law governing armed entirely leans on the need to distinguish civilians and civilian objects from the military and military objects and objectives. This is embedded under articles 48 and 51 (4) of additional protocol 1 to the Geneva conventions. Therefore, taking all necessary laws, conventions and treaties into consideration, this research paper will show how the use of autonomous weapon systems in armed conflict is a threat to the observance of the principles of international humanitarian law does, placing emphasis on how the use of these autonomous weapon systems defies and limits the actual implementation of the principles above that govern the law of war.
Undergraduate